On the stability of relativistic two-component AGN jets - Sinnis, Charalampos; Millas, Dimitrios; Vlahakis, Nektarios (OUP, 2023)
A number of observations of astrophysical jets, at different scales, have shown that jets are often non-uniform outflows in their cross-section. Their structure is believed to play an important role in their overall stability. In this work, we combine analytical methods and numerical simulations to investigate the stability of non-uniform jets originating from active galactic nuclei. We adopt a standard 'spine and sheath' model, using a fast, light inner spine and a heavier, slower outer sheath. In the first part of this work, we conduct a linear stability analysis, finding the time-scales for the growth of the instabilities and the corresponding eigenfunctions. We focus on the nature of the physical processes that dominate and drive the destabilization of configurations. In the second part, we examine the evolution of the perturbed jets through relativistic 3D numerical simulations using the PLUTO code. Starting with the eigenfunctions found in the first part as initial conditions, we derive instability growth times and evolution which are in good agreement with the linear analysis.
Keywords: (magnetohydrodynamics) MHD - methods: analytical; galaxies: active; galaxies: jets; INSTABILITIES; methods: numerical